Audit Sistem Informasi Absensi Menggunakan Aplikasi Jaktem Framework Cobit 5 - Yuliani Kartika Sasqia Putri; Eva Zuraidah (STMIK Budi Darma, 2023)
At PT Bank DKI, there are problems with Standard Operation attendance, there are still deficiencies, operations using the application in an orderly and correct manner, and there are no warnings when we are late for being absent from work. In addition to the drawbacks, there are also advantages where if we apply for leave, we can go directly through the Jaktem application, here employees can directly connect to Hcis for the process of submitting leave. Based on the results of the research that the author has done regarding auditing employee attendance information systems at PT Bank DKI with the COBIT 5 framework, the implementation of auditing with the subdomain used has reached the target level expected and reached the target, the results of the calculation of the GAP or gaps show that for the DSS01 and MEA 01 domains, the expected target level has been reached. That is above the target level 4, namely DSS01.01 manturity level 14.32, target level 5 and gap value 9.32 DSS01.02 manturity level 14.50 target level 5 gap value 9.50, DSS01.03 manturity level 14.47, target level 5 gap value 9.47 DSS01.04 maturity level 14.46, target level 5 gap value 9.47 MEA01.01 maturity level 20.3 0 manturity level target value 5, gap value 15.30, MEA01.02 manturity level 20.49 manturity target 5 gap value 15.49, MEA01.03 manturity level 20.80 target level 5 gap value 15.49, MEA01.04 maturity level 20.80 target level 5 gap value 15.80, MEA01.05 maturity level 21.14 target level 5 gap value of 16.14, from the audit result rating scale included in level F which indicates that the Fully achieved value has been achieved where there is a complete and systematic approach and full achievement